Study of Vegetative Propagation on Pericopsis mooniana THW with Cutting STUDI PEMBIAKAN VEGETATIF PADA KAYU KUKU (Pericopsis mooniana THW) MELALUI CUTTING - Andi Sukendro; Wulan Dwi Ayuning Putri (Jurnal Silvikultur Tropika, 2016)
Kayu kuku (Pericopsis mooniana THW) is one of the vancy wood species which grow naturally in Borneo and Sulawesi territory. The plants propagation through cutting has been done as the alternative of kayu kuku cultivation. This study aims to find the alternative of kayu kuku propagation through tip and stem cuttings, to discover the effectiveness of tip and stem cuttings as the techniques of kayu kuku seed production, and to discover the effectiveness of plant growth regulator IBA (Indole Butyric Acid) low concentration, IBA high concentration, and Rootone-F towards the growth of kayu kuku cutting’s root. Experimental design used on this study was Completely Randomized Desain with factorial including two factors, such as material and provision of plant growth regulator factors. The material used are bud and stem, meanwhile the PGR used are IBA 0 ppm (control), 20 ppm, 40 ppm, 60 ppm, 1000 ppm, 1500 ppm, and Rootone-F. The result of the study indicates that the utilization of tip as the cuttings material is more effective with the live and rooted percentage of 70.48% and 14.29%. The IBA provision of 60 ppm generates percentage of live and the optimum amount of secondary root of 66.67% and 6. Percentage of root is only on stem. The IBA provision of 60 ppm tends to be more effective to be used for the growth of kayu kuku cutting’s root compared to other treatments.Key words: cutting, kayu kuku, plant growth regulator